(untitled) (Research, Society and Development, 2020)
The use of growth regulators is essential for the success of mangiculture in Brazil, since they play an important role in floral induction, allowing the staggering of production throughout the year and obtaining good quality fruits and quantities that meet the internal demand and external. Due to the great economic importance of the mango, this review aims to clarify aspects about the use of paclobutrazol in inducing the flowering of the mango. The methodology adopted was the bibliographic study, and the information was obtained from documentary sources. It was found that temperature is the most important climatic factor for the flowering of the mango tree because low temperatures paralyze the vegetative growth that is indispensable for flowering. Gibberellins (GAs) are plant hormones that regulate flowering, in high concentrations favor vegetative growth and in low concentrations inside the branches induce flowering. Therefore, products that interfere in the synthesis of GAs are efficient in inducing flowering and among the products that inhibit GAs, paclobutrazol (PBZ) is the most used in mango production. It is applied to moist soil after two outbreaks of plant sprouting, therefore pruning after harvest is essential for these shoots to be vigorous and uniform. For many traditionally mango producing regions, the doses of PBZ have already been defined and depend on the cultivar, soil type, cultivation conditions, in addition to the nutritional condition of the plants and vary from 0.3 to 1.62 grams per linear meter of the canopy. For the success of floral induction of the mango tree, the application of PBZ must be combined with other managements such as pruning, mineral nutrition and irrigation.